Exploring Speech Delay in a Premature Five-Year-Old Child:An Integrative Psycholinguistic Case Analysis - Jumerli Ariati; Tengku Nindy Ananda Putri; Vinny Fiona; Dea Anggraini; Refy Aprilia (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Premature birth is a well-established biological risk factor for neurodevelopmental delay; however, limited research integrates neurological vulnerability with psycholinguistic processing mechanisms at preschool age. This study explores how prematurity contributes to speech delay in a five-year-old child through an integrative psycholinguistic framework. Using a qualitative instrumental case study design, data were collected through semi-structured parental interviews, clinical observation records, and speech-language therapy documentation. Thematic analysis revealed five dimensions of psycholinguistic impairment: lexical limitation, delayed lexical retrieval, phonological encoding weakness, sentence formulation deficit, and environmental reinforcement gap. Findings indicate that disrupted white matter development and cognitive processing inefficiencies manifest as restricted vocabulary, delayed lexical retrieval, reduced sentence complexity, and minimal communicative responsiveness. Importantly, environmental inconsistency in parental language stimulation intensifies these deficits, suggesting a dual-risk interaction between biological and environmental factors. This study proposes a conceptual framework linking prematurity, psycholinguistic processing limitations, and observable speech delay behaviours. The findings extend existing literature by providing a theoretically integrated explanation of language delay at a critical developmental milestone—age five—when school readiness becomes linguistically demanding in the Indonesian educational context. Implications emphasize early detection, structured intervention, and consistent caregiver-mediated language enrichment.